Development of Sunscreen Lotion from PKO–VCO with Surfactant Variation and Combined TiO₂ and Palm Leaf Ethanol Extract Actives - Khansa Jihan Safitri; Wydia Soffiyah; Alda Nathasya; Reni Astuti Widyowanti (G-Tech: Jurnal Teknologi Terapan, 2026)
High exposure to ultraviolet radiation in the tropics increases the risk of skin damage, making it necessary to develop an effective and stable sunscreen lotion. This study aimed to analyze the effects of Tween 80:cetyl alcohol surfactant combinations and combined active ingredients of titanium dioxide (TiO₂) and palm leaf ethanol extract on the physical characteristics and functional activity of PKO- and VCO-based lotions. The study employed a 3×3 factorial Randomized Complete Block Design (RCBD) with two replications, resulting in 18 treatment combinations consisting of variations in surfactant ratios and active ingredient concentrations. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The parameters evaluated included viscosity, pH, specific gravity, homogeneity, organoleptic properties, SPF value, and antioxidant activity using the DPPH method. The results showed that surfactants significantly affected viscosity, pH, and specific gravity, while active ingredients significantly influenced SPF value and antioxidant activity. The highest SPF value was obtained in treatment A3B2 with a value of 4.30, which was categorized as minimal protection according to the FDA sunscreen classification, while the highest and lowest antioxidant activities were 95.51% and 87.97%, respectively. All formulations showed good homogeneity and pH values suitable for skin application. Overall, the optimum formulation combination produced lotion with good physical stability, high antioxidant activity, and potential to be developed as a natural sunscreen.